Thermal and acoustic comfort in buildings - Silva, Sandra Monteiro (2010)
To achieve an adequate quality of buildings it is necessary to consider a set of aspects that are interconnected and influence each other, not always in a favourable way. The selection of the most suitable construction solution for the building elements must consider its contribution to the thermal and acoustic comfort inside the buildings, the daylight conditions, its energy efficiency and sustainability, and also the weight of the solution and its effect on the structural project of the building. In this work, the use of a multi-criteria analysis, to balance all these aspects on the design phase, in order to assist the designer in the selection of construction solutions and materials, will be presented. The selection of the most adequate construction solutions will increase the buildings thermal and acoustic behaviour and also its energy performance and sustainability.